Holozyklie und Anholozyklie bei der Schwarzen Bohnen- oder Rübenblattlaus Aphis fabae Scop. im Vergleich mit anderen Aphididae. - Müller, Fritz Paul; Jennerjahn, Ingrid (Contributions to Entomology = Beiträge zur Entomologie, 1989)
A clone of Aphis fabae sensu stricto whose rearing by artificially induced uninterrupted parthenogenesis was started by H. J. Müller in 1948, had not lost its property of holocycly even in the course of 38 years permanent parthenogenesis. All examined sources of A. fabae fabae, A. f. cirsiiacanthoidis Scop., A. f. solanella Theobald. and A. f. evonymi F. from the territory of the GDR finished the year cycle in the field insectary by producing 100% sexuales without residual viviparae thus displying to obligatory holocycle. A survey of the various manifestations of morph appearance in Aphididae in natural environment is given.